Internal Controls of the Municipality of Plaridel, Bulacan towards Good Governance - Velasco, Jerome (Future Science / FSH-PH Publications, 2021)
Internal control plays a vital role in both private and public sectors. It is considered as one of the strategic tools in improving the operations and performance of an organization that will lead to the attainment of organizational goal and objectives. The main objective of the study was to determine the impact of control activities to the Municipality of Plaridel, Bulacan in complying with the good governance criteria. An assessment was conducted to determine the extent of control activities’ implementation in the organization to come up with the recommended measures for its further improvement. The study was based on a descriptive research design involving quantitative approach. Data gathered have been processed statistically using the SPSS by the Centro Escolar University Data Processing Center, and presented using the mean, standard deviation, and Pearson correlation analysis. The overall analysis revealed that the relationship between the extent of implementation and perceived impact of control activities to the Municipality in complying with the good governance criteria has a very significant relationship rating. Findings also showed that the existing implementation of control activities in the municipality can be further improved using the recommended measures focused on the following: Revisiting and Revising the existing policies and procedures, Strengthening the top Management’s functions, and Continuous professional development. It can be concluded that the implementation of control activities in the Municipality can improve the operations, and can contribute to the compliance with the Seal of Good Local Governance Criteria - financial administration aspect.